2021
DOI: 10.4103/jrms.jrms_1256_20
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of salivary C-reactive protein and interleukin-18 for the diagnosis of neonatal sepsis

Abstract: Background: Neonatal sepsis is a leading cause of death in neonates worldwide. The investigation of biomarkers for the early diagnosis of neonatal sepsis is in progress with controversial outcomes. The current report aims to evaluate the values of salivary C-reactive protein (CRP) and interleukin-18 (IL-18) for the diagnosis of neonatal sepsis. Materials and Methods: In this cross-sectional study, 89 neonates, including 49 neonatal septic case and 40 healthy group admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Moreover, Murugesan and Rai 15 concluded that salivary CRP correlated relatively well with serum CRP based on their findings that CRP levels were considerably higher in septic newborns. Also, Barekatain et al 16 assessed salivary CRP and IL-18 to help in the early detection of neonatal sepsis, and concluded that salivary CRP may be used as a biomarker with a sensitivity of 49% and a specificity of 80% in the diagnosis of the condition. In addition to Datlaet al, there are many more.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Murugesan and Rai 15 concluded that salivary CRP correlated relatively well with serum CRP based on their findings that CRP levels were considerably higher in septic newborns. Also, Barekatain et al 16 assessed salivary CRP and IL-18 to help in the early detection of neonatal sepsis, and concluded that salivary CRP may be used as a biomarker with a sensitivity of 49% and a specificity of 80% in the diagnosis of the condition. In addition to Datlaet al, there are many more.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies showed that serum IL-18 levels were up-regulated in adult patients with sepsis. 15 , 16 In terms of neonates, only one study reported that salivary IL-18 level was not a viable biomarker for the early neonatal sepsis diagnosis, 17 while there has not been any research on the relationship between serum IL-18 levels and neonatal sepsis. Accordingly, we envisioned in the present research to evaluate the clinical value of serum IL-18 level for its application as a potential biomarker in neonatal sepsis diagnosis and predicting mortality.…”
Section: Introductionmentioning
confidence: 99%